Infection reduces anti-predator behaviors in house finches - Adelman, James S. (J. Avian Biol., 2017)
Infectious diseases can cause host mortality through direct or indirect mechanisms, including altered behavior. Diminished anti-predator behavior is among the most-studied causes of indirect mortality during infection, particularly for systems in which a parasite’s life-cycle requires transmission from prey to predator. Significantly less work has examined whether directly-transmitted parasites and pathogens also reduce anti-predator behaviors. Here we test whether the directly-transmitted bacterial pathogen, Mycoplasma gallisepticum (MG), reduces responses to predation-related stimuli in house finches (Haemorhous mexicanus). MG causes conjunctivitis and reduces survival among free-living finches, but rarely causes mortality in captivity, suggesting a role for indirect mechanisms. Wild-caught finches were individually housed in captivity and exposed to the following treatments: 1) visual presence of a stuffed, mounted predator (a Cooper’s Hawk (Accipiter cooperii)) or control object (a vase or a stuffed, mounted mallard duck (Anas platyrhynchos)), 2) vocalizations of the same predator and non-predator, 3) approach of a researcher to enclosures, and 4) simulated predator attack (capture by hand). MG infection reduced anti-predator responses during visual exposure to a mounted predator and simulated predator attack, even for birds without detectable visual obstruction from conjunctivitis. However, MG infection did not significantly alter responses during human approach or audio playback. These results are consistent with the hypothesis that predation plays a role in MG-induced mortality in the wild, with reduced locomotion, a common form of sickness behavior for many taxa, as a likely mechanism. Our results therefore suggest that additional research on the role of sickness behaviors in predation could prove illuminating.